The Application of An Intelligent Adaptive Controller for Permanent Magnet Synchronous Motor Drive Using Neural Network - Hadoud, Abdalkarim; Elgargni, Milad; Elgargani, Tareq; Abid, Salem (Conference On Engineering Science and Technology, 2021)
Electrical motors are designed to operate with high performance and precision while a fast response is achieved by the intended control. Compared to traditional synchronous motors, permanent magnet synchronous motors have complicated mathematical and non-liner models when considering control design. Designing traditional control system becomes more difficult especially when dealing with the interactive parameters. Moreover, the neural network control systems have been a topic of interest since they can be implemented for non-liner and complicated systems without considering the mathematical model of the proposed system. In order to obtain a desired response, the design is achieved through procedure called training the network based on the model. Therefore, this paper presents an implementation of a neural network for a permanent magnet synchronous motors control where improvement of the performance of control is achieved and compared with conventional proportional-integral control. The Matlab/Simulink tool box is used to simulate the proposed system. Simulation results have shown that the suggested controller provides better response than traditional proportional-integral controller for the speed control for synchronous motor driver. In addition, the speed/torque of the selected permanent magnet synchronous motor can be controlled as a desired
Keywords: An Intelligent Adaptive Controller; Artificial Neural Network; Proportional-Integral Controller; Permanent Magnet Synchronous Motor Driver